MOUTHWASH FORMULATION OF ONION (ALLIUM CEPA L.) METHANOL EXTRACT FOR INHIBITING THE GROWTH OF STREPTOCCUS MUTANS BACTERIA - Supriyanto, Sugeng; Kiromah, Naelaz Zukhruf Wakhidatul; Purwanti, Ery; Rahayu, Titi Pudji (Jurnal Farmasi Sains dan Praktis, 2024)
Dental and oral problems experienced a significant increase from 2007 to 2018. Based on the results of basic health research, dental and oral problems increased from 23.2% to 57.6%. Dental caries is ranked sixth with a prevalence of 60% to 80%. The main cause of dental caries is Streptococcus mutans. The use of mouthwash with synthetic active ingredients can cause side effects. In addition, only a few mouthwashes were able to inhibit the growth of Streptococcus mutans bacteria. The purpose of this study was to make a mouthwash formulation from onion methanol extract and to determine its ability to inhibit the growth of Streptococcus mutans bacteria. Three mouthwash formulas were made with 10%, 20% and 30% extract concentrations respectively, then physical evaluation was carried out for 14 days on days 0, 7 and 14. Physical evaluation included stability tests (odor, taste, turbidity and precipitate), pH and diameter of inhibition. The results of the formula stability evaluation on day 14 there was a change in formulas 2 and 3 color, but not in formula 1. This was due to differences in the concentration of extracts and the sappans color stability in the formulas. The pH test results for each formula are in the range of 6.0-6.3. A good mouthwash has a pH close to neutral like the pH of the mouth, which is 6-7. The results of the diameter inhibition test ranged from 6-8 mm. A significant difference was seen between the positive controls with formulas 1 and 3, but there was no significant difference between formulas 1 and 3. The conclusion of this study was that the mouthwash of onion methanol extract had the ability to inhibit the growth of Streptococcus mutans bacteria with moderate strength and the best formula was mouthwash with 10% extract concentration.